2015
DOI: 10.1371/journal.pone.0132401
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of Tobacco Smoking Prevalence and Description of Tobacco Control Strategies in Sub-Saharan African Countries; 2007 to 2014

Abstract: ObjectiveTo systematically review current smoking prevalence among adults in sub-Saharan Africa from 2007 to May 2014 and to describe the context of tobacco control strategies in these countries.Data SourcesFive databases, Medline, Embase, Africa-wide Information, Cinahl Plus, and Global Health were searched using a systematic search strategy. There were no language restrictions.Study Selection26 included studies measured current smoking prevalence in nationally representative adult populations in sub-Saharan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
119
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 33 publications
16
119
0
5
Order By: Relevance
“…Due to decreasing tobacco consumption in HICs, industries may target markets in LDCs and LMICs in the Asian-Pacific, African and Middle Eastern regions where consumption is currently on the rise [10], with Africa as the continent predicted to have the highest increases in smoking prevalence [6,21]. Although gender gaps have narrowed regarding smoking prevalence in most HICs and parts of Latin America and Eastern Europe, female smoking prevalence remains lower than male smoking prevalence in many LDCs and LMICs, encouraging industrial expansion into formerly untapped markets—recruiting non-smokers, women and children in LDCs and LMICs [5,10,25]. A study investigating gender empowerment and female-to-male smoking prevalence ratios (female empowerment as measured by economic participation and decision-making, political participation and decision-making, and power over economic resources), determined that rates of female smoking were higher than males in countries with higher female empowerment [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to decreasing tobacco consumption in HICs, industries may target markets in LDCs and LMICs in the Asian-Pacific, African and Middle Eastern regions where consumption is currently on the rise [10], with Africa as the continent predicted to have the highest increases in smoking prevalence [6,21]. Although gender gaps have narrowed regarding smoking prevalence in most HICs and parts of Latin America and Eastern Europe, female smoking prevalence remains lower than male smoking prevalence in many LDCs and LMICs, encouraging industrial expansion into formerly untapped markets—recruiting non-smokers, women and children in LDCs and LMICs [5,10,25]. A study investigating gender empowerment and female-to-male smoking prevalence ratios (female empowerment as measured by economic participation and decision-making, political participation and decision-making, and power over economic resources), determined that rates of female smoking were higher than males in countries with higher female empowerment [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, tobacco consumption in low and middle income countries is prevalent and such countries continue to confront growing burdens of such modern health risks. A systematic review of smoking prevalence in African adults revealed estimated male smoking prevalence in rural areas up to 22.8% in Rwanda and 40.4% in Zambia [5]. Without implementation and enforcement of proper tobacco control policies, global smoking prevalence could be as high as 22.0% in 2030, with the African region increasing from 15.8% in 2010 to 21.9% in 2030 [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to 2012 WHO estimates for the African region, this prevalence was almost at 22% in males and 2-3% in females, hence an overall prevalence around 12% [2]. A recent systematic review conducted by Brathwaite et al who compiled data between 2007 and 2014 from 13 SSA countries (mostly from Eastern, Western, and Southern Africa) showed that the prevalence of smoking varied immensely across SSA, from 1.8% to 25.8% [25]. …”
Section: Increasing Trends Of Tobacco Smoking and Consequential Aumentioning
confidence: 99%
“…It is worth highlighting therefore that the prevalence of tobacco use is rapidly increasing in Africa [5, 25, 26]. Indeed, we learn from Brathwaite et al that cigarette consumption in Africa and some Middle Eastern countries increased by 57% between 1990 and 2009 while it decreased by approximately 26% in Western Europe during the same period [25].…”
Section: Increasing Trends Of Tobacco Smoking and Consequential Aumentioning
confidence: 99%
See 1 more Smart Citation